ИЗМЕНЕНИЯ ФАУНИСТИЧЕСКОГО СОСТАВА ПОЗВОНОЧНЫХ ЖИВОТНЫХ КОСТАНАЙСКОЙ ОБЛАСТИ ЗА ПОСЛЕДНЕЕ СТОЛЕТИЕ - Брагина, Т.М.; Брагин, Е.А. (My University, 2019)
Аннотация В данной работе приводятся сведения об изменениях фаунистического состава позво- ночных животных Костанайской области за последнее столетие. Аbstract This paper provides information on changes in the faunal composition of vertebrate animals of the Kostanay region in the last century.
Changes in the faunistic composition of the vertebral animals of the Kostanay region in the last century
Keywords: позвоночные; изменения фауны; Костанайская область; vertebrates; changes in fauna; Kostanay region